b - Tandy, Miles; Howell, Jo. (b, 2010)
This highly practical guide gives you all the ideas you need to make drama an exciting, regular and integral part of your primary school's curriculum. -- Provided by publisher
Includes index.
Keywords: Drama in education; Drama -- Study and teaching (Primary); Interdisciplinary approach in education; Education, Primary -- Curricula